Effect of bokashi dose and frequency of administration of Plant Growth Promoting Rhizobacteria (PGPR) against pest and disease attacks on Pakcoy (Brassica rapa L.) - Nik, Nikolas; Rusae, Aloysius; Naju, Egidius (Contributions of Central Research Institute for Agriculture, 2024)
Pakcoy is a horticultural plant that has nutritional content tall one. so it is in great demand by the Indonesian people, but production is decreasing. This decline was caused by several reasons factors include soil fertility, pests and diseases which reduce its quality and quantity. This research aims to determine the dose of bokashi and the frequency of PGPR spraying on the growth and yield of pakcoy plants as well as reducing the intensity of pest attacks and diseases of pakcoy plants. This research was carried out on the grounds of the Faculty of Agriculture in July – September 2022. The design used is Design Random Group (RAK) fac tory Which consists of 2 factors with each factor consists of 4 levels, namely: the first-factor b okashi (T) which consists of 4 levels, namely: T0 = control/without bokashi, T1= 1:05 kg/ polybag, T2 = 1:1 kg/ polybag, T3 = 1:1, 5 kg / polybag. while the second factor is the frequency of PGPR spraying (F) which consists of 4 levels, namely F0 = control/no PGPR spraying, F1 = 2x PGPR spraying, F2 3x PGPR spraying, and F3 4x PGPR spraying so there are 16 treatment combinations available. repeated 3 times for a total of 48 experimental units. The parameters observed include plant height, number of leaves, fresh weight of plants, economic weight of plants, intensity of pest attacks, and incidence of plant diseases. All observational data were analyzed using the Duncan Multiple Range Test (DMRT) with significant 5%. The results of the research show that the dose of box h i 1: 1.5 kg/polybag and the frequency of PGPR spraying 4 times can increase plant height, number of leaves, and plant fresh weight whereas in the treatment, 2 spraying of PGPR with bokashi 1:1 kg/polybag reduced pest intensity by 9.12% and disease incidence by 7.20%.